Perlindungan Hak Cipta Program Komputer di Indonesia - Ginting, Jamin (LAW REVIEW, 2004)
The Indonesian government has paid a serious attention to copyright protection especially in computer program. There are five illegal software distributions punished by the court because of copying illegal software. Since July 29, 2003, Copyrights Act No. 19 Year 2002 is effective to protect computer program. There are many sanctions in this regulation to protect computer program in Indonesia like arresting illegal software distributors or users by Police or Official who has been given authority by Law with or Â without owners claim report (delik biasa), The commercial court must make a decisiion within 90 days maximum since the filing computer program. Beside all of that strongers, Copyrights Act No. 19 Year 2002 have a hole of law, there is a probability for non profit institution who uses illegal computer program for limited quantity, couldn t be sue as a crimes.